Customer satisfaction PT J&T surabaya branch perspective of service quality, price and testimonials - Elis Anita Farida; Nuning Nurna Dewi (Enrichment : Journal of Management, 2023)
This study aims to analyze the effect of service quality, price and testimonials of shipping service customers on customer satisfaction of J&T Express Surabaya Branch with a total of 70 partners. This study uses three independent variables, namely service quality, price and testimonials with one dependent variable, namely customer satisfaction. The population in this study were customers or users of J&T Express Wringinanom Branch. The sample taken was 500 respondents using Non-Probability Sampling technique with Accidental Sampling approach, which is a sampling technique based on chance, that is, who happens to meet the researcher can be used as a sample. The data analysis method used is in the form of validity and reliability tests, multiple linear regression analysis, T test and F test and it was found that the overall Service Quality Variable has no positive and significant effect on Customer Satisfaction in using J & T services with a value of 0.414 greater than 0.05. The overall price variable has a positive and significant effect on customer satisfaction in using J & T services with a value of 0.033 less than 0.05. The Testimonial Variable (X3) has a t-count value of 3.099, because the t value is 3.099> t table 1.97. And the significance value is 0.023. The significance value shows a value smaller than a = 0.05 (0.023 <0.05), which means that the Testimonial variable (X3) partially affects customer satisfaction. Customer Satisfaction (X1), Price (X2) and Testimonials (X3) simultaneously affect Customer Satisfaction (Y).